An Improved Model to Calculate Pullback Force of Trenchless Horizontal Directional Drilling Pipeline. (20th January 2022) - Liang, Xiao-qiang; Hu, Da; Li, Yong-suo; Yang, Xian; Jiang, Lei; Zhang, Yun-yi
Abstract : In the pullback operation of horizontal directional drilling pipeline crossing, the existing calculation and prediction models of pullback force are relatively simple. Each pullback force maze greatly simplifies the wellbore trajectory and fails to make a detailed analysis of the pipeline stress and external resistance when the pipeline is pulled back in each characteristic trajectory area. The factors considered are relatively simple. Therefore, it is necessary to improve the calculation method of pullback force. This paper aims to establish an improved model, enhancing the earth pressure calculation method of unloading arch and winch calculation method, and carries out an example calculation of the improved formula. Therefore, it is necessary to study the pullback process of horizontal directional drilling pipeline. Firstly, this paper analyzes the calculation method of pullback force in horizontal directional drilling; studies the calculation formula and principle of common pullback force through examples; obtains the advantages, disadvantages, and applicable scope of different formulas; and improves the calculation model of pullback force and step resistance. The numerical simulation of the step crossing process is carried out, and the variation law of local stress and strain of the pipeline and relevant conclusions are obtained. The results show that the estimates of the winch calculation method are close to the actual pullback load of the project. The earth pressure calculation method of the unloading arch and the winch calculation method are improved, and a more stable and reliable calculation formula is obtained, which provides more valuable calculation data for the actual project. In the process of pullback, the pipeline will encounter step resistance after passing through the soft and hard staggered stratum, which will suddenly increase the increment of pipeline pullback force and lead to engineering accidents. If the pullback load suddenly increases and then decreases, it may encounter similar pipeline collision accidents. At the same time, emergency measures can be taken to prevent the crossing accident and ensure the safe pullback of the pipeline.